Respostas

2014-05-09T18:08:56-03:00
É só jogar na formula

Soma = {(primeiro termo + Y termo) x Y} / 2
1 2 1
  • Usuário do Brainly
2014-05-10T11:50:17-03:00
An (termo geral) = ?
a1 (1° termo) = 5
n (número de termos) = 5
r (razão) = 3

an = a1 + (n - 1) . r
an = 5 + (5 - 1) . 3
an = 5 + 4 . 3
an = 5 + 12
an = 17

PA (5, 8, 11, 14, 17)

an (termo geral) = ?
a1 (1° termo) = 10
n (número de termos) = 5
r (razão) = - 2

an = a1 + (n - 1) . r
an = 10 + (5 - 1) . (- 2)
an = 10 + 4 . (- 2)
an = 10 - 8
an = 2

PA (10, 8, 6, 4, 2)

an (termo geral) = ?
a1 (1° termo) = 15
n (número de termos) = 5
r (razão) = 2

an = a1 + (n - 1) . r
an = 15 + (5 - 1) . 2
an = 15 + 4 . 2
an = 15 + 8
an = 23

PA (15, 17, 19, 21, 23)

an (termo geral) = ?
a1 (1° termo) = 2
n (número de termos) = 5
r (razão) = 7

an = a1 + (n - 1) . r
an = 2 + (5 - 1) . 7
an = 2 + 4 . 7
an = 2 + 28
an = 30

PA (2, 9, 16, 23, 30)